2021
DOI: 10.3390/toxics9100259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Compounds on Arsenic Metabolism and Toxicity. Part II—Human Studies

Abstract: Exposure to various forms of arsenic (As), the source of which may be environmental as well as occupational exposure, is associated with many adverse health effects. Therefore, methods to reduce the adverse effects of As on the human body are being sought. Research in this area focuses, among other topics, on the dietary compounds that are involved in the metabolism of this element. Therefore, the aim of this review was to analyze the influence of methionine, betaine, choline, folic acid, vitamin B2, B6, B12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Methionine; vitamins B2, B6, and B12; folate; and zinc are cofactors and donors of methyl groups in the metabolic changes of iAs to MMA and DMA. Many studies have reported correlations between the efficiency of iAs methylation and the spectrum of adverse changes associated with iAs exposure [ 21 ]. Thus, the relationships observed between dietary intake and the signal intensity of the metabolites may also indirectly reflect the efficiency of methylation and thus the severity of the adverse changes associated with iAs exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methionine; vitamins B2, B6, and B12; folate; and zinc are cofactors and donors of methyl groups in the metabolic changes of iAs to MMA and DMA. Many studies have reported correlations between the efficiency of iAs methylation and the spectrum of adverse changes associated with iAs exposure [ 21 ]. Thus, the relationships observed between dietary intake and the signal intensity of the metabolites may also indirectly reflect the efficiency of methylation and thus the severity of the adverse changes associated with iAs exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, both on animal models and human populations exposed to iAs primarily via drinking water, have focused on the relationship between the intake of nutrients and the concentration of As metabolites in the urine. Some studies have shown that these nutrients can improve the efficiency of iAs metabolism (observed as decreased concentrations of iAs and MMA and an increased urinary DMA concentration) and reduce adverse health effects, but not all studies have provided conclusive results [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports have demonstrated a strong association between adequate nutritional folate status and improved arsenic methylation markers (i.e., lower percentage of iAs, lower percentage of MMA V , and/or higher percentage of DMA V ) along with a lower risk for arsenic-induced toxicities (e.g., skin lesions). Studies investigating the potential role of folate and other dietary compounds in arsenic methylation have been recently summarized and reviewed in comprehensive articles (92,93).…”
Section: Nutritional Status and Dietary Intakementioning
confidence: 99%
“…For instance, in the latest review, some studies propose that nutrients participating in iAs metabolism may affect methylation efficiency. However, the research findings are not entirely conclusive [ 14 ]. They mainly concentrate on the correlation between nutrient intake and the concentration of arsenic metabolites in urine or the risk of developing diseases.…”
Section: Introductionmentioning
confidence: 99%